Pengaruh Lingkungan Kerja, Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Pegawai Di Kantor Kecamatan Tambak Kabupaten Gresik - Rizal, Fahmi; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract It turns out that the services provided by employees at the Tambak District Office still show indications that employee discipline for work is not being carried out well, which has an impact on employee performance. Based on this phenomenon, the author felt interested and challenged to conduct research to see how much influence the work environment, organizational culture and leadership actually have on employee performance. The type of research used in this research is explanatory research with a quantitative approach. The population of this study were all employees of the Tambak sub-district office, Gresik district with a sample of 41 respondents. The analysis technique used is multiple linear regression and hypothesis testing using SPSS for Windows software. The conclusion of this research is that the work environment, organizational culture and leadership simultaneously and partially have a significant effect on employee performance. Keywords: Work environment, Organizational culture, Leadership, Employee performance.